Diana, Princess of Wales a tribute - Graham, Tim 1948- (Weidenfeld & Nicalson, 1997)
Diana was many things to many people - tireless charity worker, style icon, loving mother - and this book shows the many facets of her personality in a lavish photographic tribute by Tim Graham who, from the earliest days, witnessed at close hand the making of a legend.